1981
DOI: 10.1111/j.1745-4603.1981.tb00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Texture Changes and Storage of Rice

Abstract: Monthly texture assessments of seven milled rices, differing in amylose content and stored at 28–30°C, verified that three months was the minimum storage period for major changes to occur in hardness of cooked rice, gel consistency, and amylograph viscosity values. Therefore, texture measurements should be done on samples aged at least three months after harvest. Texture changes tend to be greatest for high‐amylose rice with hard gel consistency and least for waxy rice. Free fatty acids were highest in stored,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 15 publications
3
31
1
1
Order By: Relevance
“…During ageing of rice grains, a number of physicochemical properties change (Villareal et al ., ; Chrastil, ; Perdon et al ., ; Zhou et al ., ). The minimum grain ageing period for major changes to occur in the hardness, gel consistency and amylograph viscosity values of cooked rice was 3 months (Perez & Juliano, ). Noomhorm et al .…”
Section: Introductionmentioning
confidence: 99%
“…During ageing of rice grains, a number of physicochemical properties change (Villareal et al ., ; Chrastil, ; Perdon et al ., ; Zhou et al ., ). The minimum grain ageing period for major changes to occur in the hardness, gel consistency and amylograph viscosity values of cooked rice was 3 months (Perez & Juliano, ). Noomhorm et al .…”
Section: Introductionmentioning
confidence: 99%
“…Storage of rice results in changes to its properties such as swelling; three months of storage is regarded as the minimum period required to elicit major changes in the hardness of cooked rice (Katekhong & Charoenrein 2012). Perez and Juliano (1981) as well as Daniels et al (1998) reported that rapid changes occurred in stored rice in the first six weeks and first month, respectively. The data recorded in this experiment revealed an increased peak with increased storage duration in contrast to the conclusions reported by Katekhong and Charoenrein (2012).…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen has been found to be superior to air for preserving the palatability of cooked rice during brown rice storage at 10°C for two years; however, no significant difference in quality was found between brown rice stored in nitrogen and that stored in carbon dioxide (Juliano, 1985a). Storage in nitrogen has little effect on the texture of rice, in comparison with storage in air (Perez and Juliano, 1981). The hermetic storage of milled rice at 30°C for three months under vacuum or in nitrogen, carbon dioxide, or ambient conditions has little effect on sugar levels, fat acidity, texturometer hardness, or the adhesiveness of cooked rice at 14.7% storage moisture (Yanai et al, 1979).…”
Section: Factors and Conditions During Storagementioning
confidence: 99%
“…The hermetic storage of milled rice at 30°C for three months under vacuum or in nitrogen, carbon dioxide, or ambient conditions has little effect on sugar levels, fat acidity, texturometer hardness, or the adhesiveness of cooked rice at 14.7% storage moisture (Yanai et al, 1979). At 15°C, aging effects are most significant during the first three to four months of storage (Perez and Juliano, 1981). Tensile strength, crushing, breaking hardness, and resistance to grinding increase after aging (Kondo and Okamura, 1937;Kunze and Choudhury, 1972).…”
Section: Factors and Conditions During Storagementioning
confidence: 99%